Numerical methods for engineers (fifth edition). Steven Chapra and Raymond Canale. Mc Graw Hill, 2005 - Gaudiani, Adriana Angélica (2008)
With this book, the same as in previous editions, Chapra and Canale intend to provide a solid training in numerical methods by means of a pleasant and attractive approach that motivates the reader to study the subject and enjoy while doing it. The authors use programming as a powerful tool to implement models and experiment with them, generating a greater enthusiasm on the reader and, as a consequence, a better understanding of the problems developed, which are applied to Engineering and Physics.